Dapagliflozin has No Protective Effect on Experimental Pulmonary Arterial Hypertension and Pulmonary Trunk Banding Rat Models - Li, Huayang; Zhang, Yitao; Wang, Shunjun; Yue, Yuan; Liu, Quan; Huang, Suiqing; Peng, Huajing; Zhang, Yi; Zeng, Weijie; Wu, Zhongkai (Frontiers in Pharmacology, 2021)
Sodium-glucose cotransporter-2 (SGLT2) inhibitors, a novel class of hypoglycemic drugs, show excellent cardiovascular benefits, and have further improved heart failure outcomes, significantly reducing cardiovascular and all-cause mortality irrespective of diabetes status. However, the efficacy of SGLT2 inhibitors in pulmonary arterial hypertension (PAH) and right ventricular (RV) dysfunction remains unknown. This study aimed to evaluate the effects of dapagliflozin in rats with PAH and RV dysfunction. PAH was induced in rats by monocrotaline (MCT) subcutaneous injection (60 mg/kg). Isolated RV dysfunction was induced in another group of rats by pulmonary trunk banding (PTB). Dapagliflozin (1.5 mg/kg) was administered daily via oral gavage one day (prevention groups) or two weeks (reversal groups) after modeling. Echocardiography and hemodynamic assessments were used to observe pulmonary vascular resistance and RV function. Histological staining was used to observe pulmonary vascular and RV remodeling. As compared with MCT group, dapagliflozin treatment did not significantly improve the survival of rats. Pulmonary arterial media wall thickness in MCT group was significantly increased, but dapagliflozin did not significantly improved vascular remodeling both in the prevention group and reversal group. In MCT group, RV hypertrophy index, RV area, the fibrosis of RV increased significantly, and RV function decreased significantly. Consistently, dapagliflozin did not show protective effect on the RV remodeling and function. In the PTB model, we also did not find the direct effect of dapagliflozin on the RV. This is a negative therapeutic experiment, suggesting human trials with dapagliflozin for PAH or RV failure should be cautious.